KAJIAN TEKNOLOGI ENZYM REVOLUSI AGRO DAN PENGELOLAAN TANAMAN TERPADU DI SULAWESI SELATAN - Arafah ;; Sahardi ; (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2007)
Technological study of agro-enzyme revolution and integrated crop management in South Sulawesi was carried out to know the effectiveness and efficiency of Enzyme Revolutionize Agro and PTT as opposed to the increase of paddy products and farmers' earnings. This study was executed in Tabaringan Village, Sub District Galesong Utara, and District Takalar from the plantation date 16 May to the harvest date 11 August 2006. This study was done on farmers' farms with the following treatment formula: (1) Enzyme, (2) PTT and (3) Non Enzyme. The results of the study indicated that the highest production of rice was obtained at the PTT treatment which was equal to 8.800 kg/ha compared to Enzyme treatment and Non Enzyme treatment which produced only 7.040 kg/ha. The highest production cost obtained at Enzyme treatment that was equal to Rp.8.526.224,- followed by PTT treatment that was equal to Rp.5.850.280,- and the lowest at Non-Enzyme treatment which yielded Rp.5.551.224,-. The efficiency of production cost at PTT treatment was 31.38% higher compared to Enzyme treatment. The highest farmers' earnings was obtained at PTT treatment that was equal to Rp.9.989.720,-/ha, while at Enzyme and non Enzyme treatments reached Rp.4.145.776,- and Rp.7.120.776,- /ha respectively. Therefore, the provision of Enzyme it self in form of bio-culture cannot improve the paddy productions and further does not give any benefit for the farmers. Keywords: enzym, 1CM, productivity, farmer income Kajian teknologi enzym revolusi agro dan pengelolaan tanaman terpadu di Sulawesi Selatan dilaksanakan dengan tujuan untuk mengetahui tingkat efektivitas dan efisiensi Enzym Revolusi Agro dan PTT terhadap peningkatan produksi padi dan pendapatan petani. Kajian ini dilaksanakan di Kelurahan Tabaringan, Kecamatan Galesong Utara, Kabupaten Takalar, tanam tanggal 16 Mei dan panen tanggal 11 Agustus 2006. Kajian ini dilaksanakan di lahan petani dengan susunan perlakuan: (1) Enzym, (2) PTT dan (3) Non Enzym. Hasil kajian menunjukkan bahwa hasil gabah tertinggi diperoleh pada perlakuan PTT yaitu sebesar 8.800 kg/ha, sedangkan pada perlakuan Enzym dan Non Enzym hanya 7.040 kg/ha. Biaya produksi yang paling tinggi terdapat pada perlakuan Enzym yaitu sebesar Rp.8.526.224 disusul perlakuan PTT yaitu sebesar Rp.5.850.280 dan yang paling rendah adalah pada perlakuan Non Enzym yaitu Rp.5.551.224. Pendapatan usahatani tertinggi diperoleh pada perlakuan PTT yaitu sebesar Rp.9.989.720/ha, sedangkan pada perlakuan Enzym dan Non Enzym masing-masing hanya Rp.4.145.776 dan Rp.7.120.776/ha. Dengan demikian pemberian enzym biokultur tidak meningkatkan hasil tanam padi. Kata kunci: enzym, PTT, produktivitas dan pendapatan petani